2024
DOI: 10.1038/s41598-023-47609-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of eccentric loading on performance of concrete columns reinforced with glass fiber-reinforced polymer bars

Nasim Shakouri Mahmoudabadi,
Alireza Bahrami,
Saba Saghir
et al.

Abstract: Glass fiber-reinforced polymer (GFRP) reinforcements are superior to traditional steel bars in concrete structures, particularly in vertical elements like columns, and offer significant advantages over conventional steel bars when subjected to axial and eccentric loadings. However, there is limited experimental and numerical research on the behavior of GFRP-reinforced concrete (RC) columns under eccentric loading having different spacing of stirrups. In this study, six specimens were cast under three different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The learning algorithms optimize these parameters to minimize the difference between the network's predicted outputs and the desired outputs, which is the process known as training. The weights are changed based on the difference between the target value and the predicted value [43], [44], [45]. In addition to the optimization algorithm, other factors can affect the performance of a neural network, such as the architecture of the network and the amount and quality of the training data [46].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…The learning algorithms optimize these parameters to minimize the difference between the network's predicted outputs and the desired outputs, which is the process known as training. The weights are changed based on the difference between the target value and the predicted value [43], [44], [45]. In addition to the optimization algorithm, other factors can affect the performance of a neural network, such as the architecture of the network and the amount and quality of the training data [46].…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…Becoming an effective construction material, numerous studies have been dedicated to assessing the capacity of composite structures. For instance, Shakouri Mahmoudabadi et al 23 investigated the behavior of concrete columns fortified with glass fiber-reinforced polymer bars subjected to eccentric loading using experimental and finite element analysis models. They observed that the loading capacity of the specimens declines as the eccentricity rises.…”
Section: Introductionmentioning
confidence: 99%
“…Fibers in concrete serve to enhance its mechanical properties, control cracking, and improve durability. They are essential for creating more resilient and robust structures [35][36][37]. Shape memory alloy (SMA) is a type of metal alloy that has different mechanical features that are not found in steel used for construction.…”
Section: Introductionmentioning
confidence: 99%